ESTETIKA EKSPRESI STRUKTUR DI TERMINAL PENUMPANG KAPAL LAUT - Dwi Rachma Septiani; Maria Immaculata Ririk Winandari; Julindiani Iskandar (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2020)
Structures in architecture acts as a load-bearing element on mechanical systems. In addition, structures can also provide spatial and aesthetic expressions in architectural with the use of certain techniques and materials that bring out the structure expression. The problem discuss in this paper relates to aesthetic parameters used to examine the structural expression on architectural. The research method used is descriptive analytical method conducted with study of the literature on aesthetics, based on parameters: visual complexity, texture and colour, symmetry of the form and familiarity using the case study of Ship Passenger Terminal building such as Qingdao Cruise Passanger Terminal, Kai Tak Cruise Terminal and Salerno Maritime Terminal.The result shows that visual complexity parameter were exposure the form of curved structures and folding structures, the use of lattice, single-mass, and different building imagery. The texture and colour parameter are subtle textures with curved patterns, use of aluminium or concrete materials,and ivory white to bring out the buildings with the color of the sea.The symmetry of the form parameter shows a natural scale, a rectangular geometric shape that is subjected to addition or subtraction, and the proportion 2:1 between the envelope and open façade. The familiarity parameter is repetition of asymmetric curved patterns form make rhythm that raises perception of the visual aesthetic of the building.